Karakter Religius Pada Remaja Yang Ditinggal Orang Tuanya Merantau - Roben Hendri (CV. ULIL ALBAB CORP, 2024)
As a result of economic demands and the difficulty of finding a permanent income due to unfavorable geographic conditions, as well as a lack of capital, coupled with insufficient knowledge to try, parents are forced to leave their children to become migrants. The aim of this research is to determine the factors that encourage parents to go abroad and the condition of the religious character of the teenagers they leave behind, as well as the responsibility of parents who migrate towards the religious character of the teenagers they leave behind. In terms of research methodology, the researcher used qualitative research. Meanwhile, the techniques used in collecting data are through observation, unstructured interviews and documentation. The results of this research explain that: First, there are two factors that encourage parents to migrate, including internal factors and external factors. Second, the condition of teenagers' religious character.